1990
DOI: 10.1159/000168168
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Dialysate Immunoglobulin G in Continuous Ambulatory Peritoneal Dialysis Patients: A Multicenter Study

Abstract: Peritoneal dialysate immunoglobin (Ig)G concentrations were measured in 120 continuous ambulatory peritoneal diaysis (CAPD) patients evaluated at four dialysis centers in different countries to assess the normal range for dialysate IgG and to investigate the relationships of this protein levels with peritoneal episodes, For 65 of these patients, plasma IgG levels were determined, and IgG clearances were calculated. The mean dialysate concentration of IgG was 6.9 ± 4.2 mg/dl, and there was no difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
2
1
2
Order By: Relevance
“…The median concentrations of IgG in peritoneal fluid in adults were 4.59 mg/dl (range 0.92-27.4) and 12.15 mg/dl (range 5.01-26.2) at the beginning and at the end of the study, respectively. These results are similar to those of other studies [5,17]. In addition, the median concentration of peritoneal dialysis fluid was higher in adults than in pediatric patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The median concentrations of IgG in peritoneal fluid in adults were 4.59 mg/dl (range 0.92-27.4) and 12.15 mg/dl (range 5.01-26.2) at the beginning and at the end of the study, respectively. These results are similar to those of other studies [5,17]. In addition, the median concentration of peritoneal dialysis fluid was higher in adults than in pediatric patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no correlation was found between hypogammaglobulinemia and the frequency of peritonitis in either children or adults, which supports previous studies [4,15,17,18]. The frequency of peritonitis in children was lower than in adult patients who had not had hypogamma-88 globulinemia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Peritondaki IgG düşük olduğunda, opsonik aktivitenin de düşük olması beklenirken, peritondaki IgG konsantrasyonu düşük olmaksızın opsonik aktivitenin azalabileceği de gösterilmiştir (12). IgG konsantrasyonu ile peritonit sıklığı arasında negatif korelasyon saptanan çalışmalar (13,14) varlığının yanısıra ilişki olmadığını bildiren çalışmalar da vardır (15). SAPD'de plazma ve diyalizat IgG düzeylerinin değerlendirildiği multisentrik bir çalışmada; diyalizatta ortalama IgG düzeyi 6,9±4,2 mg/dl olarak saptanmıştır ve diyalizat IgG düzeyi rezidüel renal klirens ile yakın ilişkili bulunmuştur.…”
Section: Discussionunclassified
“…Diyalizat volümü, plazma albumini ve total protein ile negatif korelasyon saptanmıştır. Peritonit sayısı ile serum ve diyalizat IgG düzeyi arasında ilişki saptanmamıştır (15). Diğer bir çalışmada da 36 SAPD hastasında serum ve diyalizat IgG, C3, albumin düzeyleri değerlendirilmiş ve peritonit riski ile korelasyon saptanamamıştır (16).…”
Section: Discussionunclassified